A Discourse of Transformative Islam within Curriculum Transformation at State Institute for Islamic Studies of Purwokerto (IAIN Purwokerto) - Sabarudin (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
This research is aimed to trace the thoughts and actions as efforts to achieve the vision and mission of state institutes for Islamic studies of Purwokerto (IAIN). The study is directed to answer the following questions. Firstly, why transformative Islam becomes a discourse on curriculum development. Secondly, how a discourse of transformative Islam implicates in curriculum development at the state institute for Islamic studies of Purwokerto (IAIN). Then, the findings show that a discourse of Islam transformative in curriculum development at state institute for Islamic studies of Purwokerto (IAIN) emerges as a result of incapability of traditional and modern Islam perspective to resolve people’s problem due to lack of critical understanding of the meaning and message of the Qur’an and Hadith. Then, the implication of Islamic transformative discourse in curriculum development at the state institute for Islamic studies of Purwokerto can be seen in its intra curricular activities, co-curricular, and extracurricular activities. Through intra-curricular activities, transformative Islam is embodied in Islamic building lectures. In the co-curricular programs, Islam is indigenized through the activity of knowledge and practice of worship (nationally abbreviated PPI), while within extra-curricular activities transformative Islamic values come into student activities which are strongly supported by policies of university leaders.